Determinan Kualitas Hasil Pemeriksaan Auditor Internal Pemerintah Daerah - Ihsan Hadi; Lilik Handajani; Alamsyah Alamsyah (Universitas Muhammadiyah Yogyakarta, Indonesia, 2017)
This study aims to examine and find the empirical evidence the effects of Competence, Independense, Obedience Pressure and Internal control System on the quality of the examination results of the internal auditor. Samples were either internal auditor Functional Auditor (JFA) and Control Officers (P2UPD) at Inspectorate province, district/city on the Lombok Island in Nusa Tenggara Barat Province. Sampling technique used is Purposive sampling so that the sample is 141 internal auditors and analysis method used is Structural Equation Modeling (SEM) by using analytical tools Partial Least Square (PLS). The results showed that the Competence and internal control system significant positive effect quality of the examination results of the internal auditor. The study also found obedience pressure can influence the role of the examination results but with a negative direction. While the independence does not affect the examination results. The implication of this research is to give opportunity to the APIP on the Lombok island to give more attention to the factors that can improve the quality of the examination results as to how to resolve the obedience pressure, keep use Internal control system, enhance the competence of the internal auditor.